Предмет: Алгебра,
автор: fa1234sd
ПОМОГИТЕ ПОЖАЛУЙСТА С ЛОГАРИФМАМИ !!! ДАЮ 30 БАЛЛОВ.
![<br />
log_{2}(x^{2}+3)+log_{\frac{1}{2}}5=2log_{\frac{1}{4}}(x-1)-log_{2}(x+1);<br /><br />
3log_{8}(x-2)=log_{2}\sqrt{2x-1};<br />
<br />
log_{2}(x^{2}+3)+log_{\frac{1}{2}}5=2log_{\frac{1}{4}}(x-1)-log_{2}(x+1);<br /><br />
3log_{8}(x-2)=log_{2}\sqrt{2x-1};<br />](https://tex.z-dn.net/?f=%3Cbr+%2F%3E%0Alog_%7B2%7D%28x%5E%7B2%7D%2B3%29%2Blog_%7B%5Cfrac%7B1%7D%7B2%7D%7D5%3D2log_%7B%5Cfrac%7B1%7D%7B4%7D%7D%28x-1%29-log_%7B2%7D%28x%2B1%29%3B%3Cbr+%2F%3E%3Cbr+%2F%3E%0A3log_%7B8%7D%28x-2%29%3Dlog_%7B2%7D%5Csqrt%7B2x-1%7D%3B%3Cbr+%2F%3E%0A)
Ответы
Автор ответа:
1
/task/29424061 ------------------------
Log₂(x²+3) +Log_1/2 5 = 2Log_1/4 (x-1) -Log₂(x+1) очевидно ОДЗ : x >1
Log₂(x²+3) +Log_1/2 5 = 2Log_1/4 (x-1) -Log₂(x+1 ) ⇔
Log₂(x²+3) - Log₂ 5 = - Log₂ (x-1) -Log₂(x+1)⇔
Log₂(x²+3) + Log₂ (x-1) +Log₂ (x+1) = Log₂ 5⇔(x²+3)(x²-1) =5 || t =x² | |⇔
(x²)² + 2x² -8 =0 ⇔ [ x² =- 4 ; x²= 2.⇔ x=√2 . * * * x=√2 >1 ∈ ОДЗ * * *
ответ: √2 .
3Log₈ (x-2) = Log₂√(2x-1) ясно ОДЗ : x > 2
3Log₈ (x-2) = Log₂√(2x-1) ⇔Log₂ (x-2) = Log₂√(2x-1) ⇔ x-2 =√(2x-1)
(x- 2 )²= 2x-1 ;
x² - 4x +4 =2x -1 ;
x² - 6x +5 =0 ;
x ₁ = 1 < 2 ∉ ОДЗ
x₂ = 5
ответ: 5 .
Похожие вопросы
Предмет: Окружающий мир,
автор: soldy21
Предмет: Английский язык,
автор: bimogarri
Предмет: Математика,
автор: veronikaageenko2020
Предмет: Математика,
автор: mimimixa
Предмет: Алгебра,
автор: про100женя12